Penerapan Pertanian Sehat Desa Bantaragung Untuk Menjaga Kelestarian Ekosistem Kawasan Taman Nasional Gunung Ciremai (TNGC) - Ismail Saleh; Raden Eviyati; Farida Mardhatilla; Siti Wahana (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
Bantaragung village, Sindangwangi sub-district, Majalengka district is one of tourist destination in West Java. This village was located near to Gunung Ciremai National Park. The purpose of application of eco-friendly farming in this village was to preserve the ecosystem around Bantaragung village and Gunung Ciremai National Park. The effort to begin eco-friendly farming in Bantaragung village by investigate the interest of people about eco-friendly farming by using questionnaire, training to make organic fertilizer from rice straw, make a pilot field of organic farming, and focus group discussion (FGD) to discuss with the farmer about the next plan in applying eco-friendly farming in this village. The result of these extension activities was the interest of farmer to using organic fertilizer increased. The growth and yield of rice in pilot field was decreased due to infertile soil and the nutrient from organic fertilizer was still unavailable to plant. It was the common thing because in applying organic farming, the yield was decreased in the first planting season. The next plans of this extension was to apply rice straw-the wastes from previous planting to the soil in order to restore the nutrient that had been absorbed by plant.